(3Md Tchc GdQGRi Ydi LGdjfhSs - (3RgQ Hf YHO Gdedc Hf eMeO Hf RgQ GdGTHjdj, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CJbf cd TF Ndbg hdeG cGfJ UfGYI GdWH CLd GdUfGYGJ, EP ehVhYgG GLSGO GdHTQ, cGf GddGRe Ydi ef MPb efgG TjFkG Cf jHPd LgOg ai TQM eG GSJZdb, hGSJfHGW eG Lgd , GhQO TGc Yf Tcg s
(3BNQgG (B:s
(3BNQg fGbU , hBNQ GdehLhO efg (B: (3GdCHOGf GdJi CJGgG GdHMQGf bO ESJZfJ Yf GdESJaQGZ, EP cGfJ GdWHjYI bO aYdJ Pdc, hEfeG JMJGL Edi Pdc GdCHOGf hcKQI GdaYd GdPi dGjDef Cf s
(3hQO GSe GdcJGH HgPG GdTcd ai WHbGJ GdCWHGAs
(3hGdPi Ydi UaMI GdYfhGf(B: (3GdHjGf hGdJHjf ai GdEfJUGQ dLGdjfhS Ydi eG CNP Ydjg aj LejY cJHgWHbGJ GdGWHGA(B64/2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B83 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs